Outperformance of CAM-B3LYP than M062X Density Functional in Mixed Transition of Local Excitation and Charge Transfer (Journal of Atomic and Molecular Sciences, 2019)
A balance between the local excitation (LE) and charge-transfer (CT) transitions is an importantissue of a density functional. In this work, we compare the performance between the global hybrid functionalM062X and long-range separated functional CAM-B3LYP when they calculate the absorption energies ofvisible light photoswitches hemithioindigo (HTI) Z1, Z2, Z4, Z5 and Z7. The electronic excitations of HTI Z1 andZ2 are mixtures of LE and CT transitions. CAM-B3LYP succeeds to predict the same absorption energysequence of the five compounds as the experimental results while M062X predicts a wrong sequence of HTIZ1 and Z2. Another global hybrid functional M06 is also employed for a comparison. Finally, we suggest CAM-B3LYP rather than M062X when dealing with mixed electronic transtions.
Keywords: Photoswitches; Hemithioindigo; Vertical Excitation Energy; Density Functional.